Cybersecurity: A Key Challenge to the Information Age in Sierra Leone - Sawaneh, Ibrahim Abdulai; Kamara, Fatmata Kanko; Kamara, Albert (Asian Journal of Interdisciplinary Research, 2021)
Humans’ growing desire to continuously interact with each other through the internet has both negative and positive consequences, especially if users tend to use it maliciously. The advent of social networking sites has broken the traditional barriers to communication. It is a cost-effective way of communicating using text-messages, video-messages, and voice-notes as it happens from a source (sender) to the audience (receivers). Anyone can participate if they have a mobile phone with internet facilities, and now, everyone is an online journalist and a reporter. Unfortunately, although social media platforms have numerous merits, these platforms still face critical challenges, especially in controlling and policing content post by users. The revolution in information technology and social networking platforms have provided a NEW NORMAL for online fraudsters and criminals. Fake news, hate speech, and political propaganda/rhetoric has created a confusing world, especially during the Covid-19 pandemic situation. Therefore, our paper presented some of the challenges and solutions to cybercrime.